2013
DOI: 10.1542/peds.2012-0043
|View full text |Cite
|
Sign up to set email alerts
|

Capture of Complexity of Specialty Care in Pediatric Cardiology by Work RVU Measures

Abstract: Time, skill, and stress inherent to performing catheterization procedures for congenital heart disease are not captured by measurement of RVU alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
(13 reference statements)
3
16
0
Order By: Relevance
“…In accordance to other published studies reporting patient radiation doses and procedure complexity [15], [16], [30], this study reports consistent fluoroscopy times used for diagnostic and interventional procedures with the two systems across the weight groups, regardless of procedure complexity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In accordance to other published studies reporting patient radiation doses and procedure complexity [15], [16], [30], this study reports consistent fluoroscopy times used for diagnostic and interventional procedures with the two systems across the weight groups, regardless of procedure complexity.…”
Section: Discussionsupporting
confidence: 89%
“…As interventional procedures become more and more complex and procedural complexity is correlated with increasing fluoroscopy exposure time, adequate radiation reduction is of specific importance [29], [30].…”
Section: Discussionmentioning
confidence: 99%
“…5 The only investigation in patients with CHD has similarly shown that CPT-based charges poorly reflect actual resource utilization in a pediatric cardiac catheterization laboratory. 6 Ours is the first study to demonstrate the poor correlation between CPT-based charges and resource utilization in pediatric/congenital echocardiography. This observation is hardly surprising given that the CPT-based system only differentiates between complete versus limited studies and between those with and without CHD.…”
Section: Discussionmentioning
confidence: 91%
“…There have been long-standing suspicions that RVU's are not a panacea to the quick fix desires of fiscal offices measuring physicians' worth, but most generalized studies have not supported those concerns [3]. Although some highly specialized procedures do appear to fall short in their RVU allotment, any increase in one current procedural terminology RVU allotment will require a reduction in other areas to keep the sum total the same as required by the RVU disbursement system, thus any changes upstream will cause a rippling effect downstream [3,4]. RVU's are supposed to measure up to the entire framework of work expended by the physician and his practice for covering that particular procedure but could fall short when the patient or family require more than the average attention level.…”
mentioning
confidence: 99%
“…It appears that the frequency of ward visits or perioperative nurse, patient, and family phone calls are immeasurable in any study produces thus far. As other authors have stated, few studies have sufficiently questioned the relationships between RVU assignment and the level of time, skill, and stress related to that procedure [4]. To make matters worse, since 1992 there has been a longstanding "perception that procedural medical services are reimbursed at an inappropriately greater rate than cognitive services."…”
mentioning
confidence: 99%